Business Innovation Towards a Circular Economy - Jan Konietzko (A+BE: Architecture and the Built Environment)
We currently live in a carbon intensive linear economy. On the basis of burning fossil fuels, we take, make and waste an increasing amount of materials. This has pushed us against serious planetary boundaries. Radical reductions in environmental impact are needed over the coming decades. Entire economies and societies will have to reorganize. A promising candidate to support this reorganizing is a circular economy. It cuts waste, emissions and pollution, and it keeps the value of products, components and materials high over time.  Companies can innovate towards a circular economy by following five key resource strategies: narrow, slow, close, regenerate, and inform. This thesis explores these strategies – through case research and a design science approach. It shows that an ecosystem perspective is necessary to implement these strategies – and provides tools and methods that can help to put an ecosystem perspective into action. This can help companies to develop circular ecosystem value propositions: that propose a positive collective outcome, fulfill user needs in exciting ways, and minimize environmental impact.